Identification of factors for developing going concern prediction models - Paul Hammond; Mustapha Osman Opoku; Paul Adjei Kwakwa (Cogent Business & Management, 2022)
The study aimed to identify factors that can be used in models that predict going concern of enterprises. The study employed the best-worst method of multi-criteria decision-making technique to evaluate and rank the factors. Twenty-one potential determinants were identified from the literature reviewed. Twelve decision-makers with rich experience and different professional backgrounds scrutinised and ranked the factors that affect going concern of organisations. A linear BWM solver was used to determine the optimal weights of each category. Liquidity and profitability ratios emerged as the two best determinants that are key in predicting going concern. The current ratio emerged as the overall critical determinant, while board independence measured as the ratio of non-executive board members to total board members popped up as the influential corporate governance variable for determining going concern. It is, therefore, recommended that going concern models should incorporate liquidity and profitability ratios as well as corporate governance issues.
Keywords: 650; best-worst method; corporate governance; financial ratios; going concern; prediction model